2020
DOI: 10.1002/aur.2289
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Cardiac Interoceptive Focus Across Development: Implications for Social Symptoms in Autism Spectrum Disorder

Abstract: Interoception involves the processing of sensory information relevant to physiological functioning and is integral to building self‐awareness, emotional states, and modulating social behaviors. With the role of interoception in emotional processing and social functioning, there is growing interest in characterizing interoception in autism spectrum disorder (ASD), yet, there are mixed results regarding cardiac interoceptive accuracy in ASD. In this study, we explored the neural basis of cardiac interoception us… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 70 publications
1
14
0
Order By: Relevance
“…Previous fMRI studies have suggested right insular dominance in interoception (Simmons et al., 2013; Zaki et al., 2012), which supports the forebrain asymmetry of sympathetic/parasympathetic processing (Craig, 2005, 2009). Other studies have reported that the bilateral insula is involved in interoceptive attention tasks; however, none of these studies directly compared the activation between the right and left insula (Failla et al., 2020; Haase et al., 2016; Wiebking et al., 2010). Regarding the asymmetry in autonomic input to the insula, the results of the current study imply that a representation of body states is established by the cooperation of sympathetic activities on the right middle‐anterior insula and by parasympathetic activities on the left.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous fMRI studies have suggested right insular dominance in interoception (Simmons et al., 2013; Zaki et al., 2012), which supports the forebrain asymmetry of sympathetic/parasympathetic processing (Craig, 2005, 2009). Other studies have reported that the bilateral insula is involved in interoceptive attention tasks; however, none of these studies directly compared the activation between the right and left insula (Failla et al., 2020; Haase et al., 2016; Wiebking et al., 2010). Regarding the asymmetry in autonomic input to the insula, the results of the current study imply that a representation of body states is established by the cooperation of sympathetic activities on the right middle‐anterior insula and by parasympathetic activities on the left.…”
Section: Discussionmentioning
confidence: 99%
“…These studies may support the view of sympathetic bodily re‐representation that occurs exclusively in the right anterior insula, but others implicitly challenge this notion. That is, studies employing the interoceptive attention paradigm have often reported the activation of the bilateral middle insula (Avery et al., 2014; Failla et al., 2020; Haase et al., 2016; Stern et al., 2017; Wiebking et al., 2010). A meta‐analysis on interoceptive attention (especially heart attention) found that the cluster was consistently activated in the bilateral (but somewhat right‐lateralized) dorsal middle insula (Schulz, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These neuroanatomic finding may implicate the possible overgrowth of interoceptive brain regions in ASD. More recently, however, a functional neuroimaging study recruited 46 ASD patients (aged between 8 and 54 years) and matched controls, and reported that no impairment of interoceptive accuracy was found in both behavioural and functional brain activation patterns (Failla et al, 2020). Further research is needed to clarify whether ASD individuals are impaired in multidimensional interoception.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, interoceptive deficits in patients with psychiatric disorders have attracted growing research interest. Abnormal interoception is believed to contribute to impairments of social cognitions found in people with anxiety disorders (Palser et al, 2018;Pollatos et al, 2009), depression (Barrett et al, 2016;Paulus & Stein, 2010), anorexia nervosa (Khalsa et al, 2018;McFadden et al, 2014), attention-deficit/hyperactivity disorder (Kutscheidt et al, 2019), schizophrenia (Ebisch et al, 2014;Torregrossa et al, 2019) and autism spectrum disorder (ASD) (Failla et al, 2020;Francis et al, 2019;Garfinkel et al, 2016;Schauder et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Neither of these studies directly compared neural activation to that in adult participants, however, meaning further work is needed to determine the full developmental trajectory. In a sample of neurotypical and autistic individuals spanning a larger age range (8–54 years), quadratic and linear relationships were observed between age and neural activation while performing the heartbeat counting task in different subdivisions of the insula, and linear relationships between age and activation in a broader interoceptive network, although age was unrelated to behavioural task performance ( Failla et al, 2020 ). Interoceptive accuracy does appear to be associated with heartbeat evoked potentials in adolescence, as in adulthood ( Mai et al, 2018 ), but again work is needed that explicitly follows the developmental trajectory throughout childhood and into adulthood.…”
Section: What Gives Rise To Poor Interoception? the Development Of Typical Interoception And How It May Go Awrymentioning
confidence: 99%